A Case of Successful Coil Embolization for a Late-Onset Type Ia Endoleak after Endovascular Aneurysm Repair with the Chimney Technique. (6th September 2016) - Igari, Kimihiro; Kudo, Toshifumi; Toyofuku, Takahiro; Inoue, Yoshinori
Abstract : Juxtarenal aortic aneurysms (JRAAs) are challenging to treat by endovascular aneurysm repair (EVAR) procedures. The chimney technique with EVAR (Ch-EVAR) is one of the feasible and less invasive treatments for JRAAs. However, the main concern of Ch-EVAR is the potential risk of "gutters, " which can lead to type Ia endoleak (EL). Most type Ia ELs after Ch-EVAR procedures occurred intraoperatively, and these ELs could be treated using an endovascular technique. However, late-onset type Ia ELs could be extremely rare, which might have a fear of conservative treatment. Type Ia ELs are associated with an increased risk of aneurysm rupture; therefore reintervention is recommended as soon as possible, and we should be aware of the occurrence of type Ia ELs after the Ch-EVAR procedure.